Indicators for mode of delivery in pregnant women with uteruses scarred by prior caesarean section: a retrospective study of 679 pregnant women - Zhifen Hua; Fadwa El Oualja (BMC, 2019)
Abstract Background The delivery mode for pregnant women with uteruses scarred by prior caesarean section (CS) is a controversial issue, even though the CS rate has risen in the past 20 years. We performed this retrospective study to identify the factors associated with preference for CS or vaginal birth after CS (VBAC). Methods Pregnant women (n = 679) with scarred uteruses from Moulay Ali Cherif Provincial Hospital, Rashidiya, Morocco, were enrolled. Gestational age, comorbidity, fetal position, gravidity and parity, abnormal amniotic fluid, macrosomia, placenta previa or abruptio, abnormal fetal presentation, premature rupture of fetal membrane with labor failure, poor progression in delivery, and fetal outcomes were recorded. Results Out of 679 pregnant women ≥28 gestational weeks, 351 (51.69%) had a preference for CS. Pregnant women showed preference for CS if they were older (95% CI 1.010-1.097), had higher gestational age (95% CI 1.024-1.286), and a shorter period had passed since the last CS (95% CI 0.842-0.992). Prior gravidity (95% CI 0.638-1.166), parity (95% CI 0.453-1.235), vaginal delivery history (95% CI 0.717-1.818), and birth weight (95% CI 1.000-1.001) did not influence CS preference. In comparison with fetal preference, maternal preference was the prior indicator for CS. Correlation analysis showed that pregnant women with longer intervals since the last CS and history of gravidity, parity, and vaginal delivery showed good progress in the first and second stages of vaginal delivery. Conclusions We concluded that maternal and gestational age and interval since the last CS promoted CS preference among pregnant women with scarred uteruses.